Effects of Big Five personality traits and market mavenship on consumers' intention to spread word-of-mouth in the art context. (2nd February 2022) - Chieffi, Verdiana; Pichierri, Marco; Peluso, Alessandro M.; Collu, Cristiana; Guido, Gianluigi
Abstract : Purpose: This study investigates the transmission of art-related aspects (i.e. art products or services and people's experiences at museums) via word-of-mouth (WOM) from a personality perspective. Specifically, the study explores the effects of the Big Five personality traits (based on the five-factor model) and market mavenship (i.e. the propensity to provide general marketplace and shopping information) on intention to spread WOM in the art context. Design/methodology/approach: Data were gathered through two field surveys, conducted via a structured questionnaire and analyzed using multiple regression analysis. Findings: Results indicate that extraversion is the only Big Five personality trait that increases WOM intention (e.g. by talking to others about a visit to a museum). Market mavenship also increases such an intention (e.g. by talking to others about art services). Practical implications: The study's findings could motivate arts managers to formulate and/or refine segmentation strategies around their consumers' personality traits, since these variables may differently motivate them to spread art-related WOM. The findings may also help companies and institutions operating in the art industry to design communication strategies oriented around their consumers' personality type to appropriately connect with different groups of customers based on their innate human drives. Originality/value: This is the first study to assess the effects of Big Five personality traits and market mavenship on WOM intention in the art context, thus expanding scholarly understanding of psychological drivers behind arts-related WOM.